A new algorithm for stope boundary optimization - Topal, Erkan; Sens, J. (Springer-Verlag and Journal of Coal Science and Engineering, 2010)
Stopes can be simply defined as an underground opening from which ore has been excavated. Selection of the best combination of available stope boundary will directly affect the profitability of the operation. While a few attempts has been initiated to generate the optimum stope boundary for underground mining, they fail to guarantee a true optimality in three-dimension block models. This paper proposed a new methodology which can find optimum stope layout for a given resource model in three-dimensions. The paper initially critically reviewed important stope boundary optimisation studies thus far, then proposed a new methodology in order to find the best stope layout for a given deposit. Subsequently it applied the proposed methodology into a block model to test its ability of producing optimum results and demonstrated its applicability in a number of different scenarios. In the last section, further analysis on strategies to find the optimum stope boundaries were demonstrated. The results prove that the proposed algorithm can find optimum stope boundaries and layouts in three-dimension for different stope sizes and stope selection strategies.